1996
DOI: 10.1143/jjap.35.l781
|View full text |Cite
|
Sign up to set email alerts
|

Size Reduction of Silver Particles in Aqueous Solution by Laser Irradiation

Abstract: The effect of pulsed laser irradiation on silver particles in aqueous solution was investigated. The particle size decreased and the size distribution became narrower after irradiation for 15 minutes using third harmonics of a pulsed YAG laser. The number of the aggregated particles also decreased after the irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 7 publications
2
41
0
2
Order By: Relevance
“…The peak at ∼720 nm corresponding to the main resonance of silver nanoprims is strongly damped by the irradiation showing the color change of the solution from blue to yellow. The distinguished plasmon resonance band at around 405 nm is related to the excitation of the surface plasmon of the silver spheres [10,18]. We also found that the longer the pulse duration, the smaller the particles size and the narrower the size distribution.…”
Section: Conversion Of Silver Nanoprisms Into Colloidal Nanoparticlesmentioning
confidence: 54%
See 1 more Smart Citation
“…The peak at ∼720 nm corresponding to the main resonance of silver nanoprims is strongly damped by the irradiation showing the color change of the solution from blue to yellow. The distinguished plasmon resonance band at around 405 nm is related to the excitation of the surface plasmon of the silver spheres [10,18]. We also found that the longer the pulse duration, the smaller the particles size and the narrower the size distribution.…”
Section: Conversion Of Silver Nanoprisms Into Colloidal Nanoparticlesmentioning
confidence: 54%
“…Since the heating is very selective, thus, the laser-induced shape change of metal nanostructures not only provide a simple means for "post-preparation" shape control but also pertain to the physically important issue of laser-nanostructure interactions and some complicated relaxation dynamics of the deposited laser energy [9]. Most of the early studies on the laser-induced change of metal nanoparticles were concentrated on the size reduction of noble metal particles, particularly gold and silver, as a breaking-down process to produce fine metal nanoparticles [10,11]. Among others, the recent laser-induced transformation studies of gold nanorods in colloidal solutions or metal-island films into spherical particles represent a particularly drastic shape change using ultrafast femtosecond or nanosecond laser pulses [12][13][14].…”
mentioning
confidence: 99%
“…This technique has been used to reduce NP size of because focused LI at high fluence has generally been conducted to induce vaporization and fragmentation of NPs [1][2][3][4][5]. Moreover, recent works have shown that LI is also applicable to increase the particle size of colloidal NPs [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many nano-scale materials exhibit unique properties that are ideal for applications in science and technology [1][2][3]. Among them gold nanoparticles (Au-NPs) appear rather promising.…”
Section: Introductionmentioning
confidence: 99%